Surmounting Cancer Drug Resistance: New Perspective on RNA-Binding Proteins - Yiyuan Feng; Sha Zhu; Tengwen Liu; Guoguo Zhi; Bingjie Shao; Jibin Liu; Baixue Li; Cen Jiang; Quansheng Feng; Peijie Wu; Dong Wang (MDPI AG, 2023)
RNA-binding proteins (RBPs), being pivotal elements in both physiological and pathological processes, possess the ability to directly impact RNA, thereby exerting a profound influence on cellular life. Furthermore, the dysregulation of RBPs not only induces alterations in the expression levels of genes associated with cancer but also impairs the occurrence of post-transcriptional regulatory mechanisms. Consequently, these circumstances can give rise to aberrations in cellular processes, ultimately resulting in alterations within the proteome. An aberrant proteome can disrupt the equilibrium between oncogenes and tumor suppressor genes, promoting cancer progression. Given their significant role in modulating gene expression and post-transcriptional regulation, directing therapeutic interventions towards RBPs represents a viable strategy for combating drug resistance in cancer treatment. RBPs possess significant potential as diagnostic and prognostic markers for diverse cancer types. Gaining comprehensive insights into the structure and functionality of RBPs, along with delving deeper into the molecular mechanisms underlying RBPs in tumor drug resistance, can enhance cancer treatment strategies and augment the prognostic outcomes for individuals afflicted with cancer.